2023
DOI: 10.1021/acs.langmuir.3c00117
|View full text |Cite
|
Sign up to set email alerts
|

Lattice Boltzmann Study of Microdroplet Evaporation Process in Pixel Pits

Abstract: Inkjet printing has the advantages of high material utilization, low cost, and large-area production and is a promising manufacturing technology for organic light-emitting diode (OLED) displays. However, the droplet evaporation in micron-size pixel pits is highly influenced by the pit wall. Such a process is extremely difficult to control, leading to the appearance of defects such as the coffee ring in the printing process of OLED displays. In this work, a multiphase thermal lattice Boltzmann (LB) model based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Sefiane and Bennacer concluded that nanofluid droplets reduced the overall evaporation time compared to base fluid droplets but prolonged the pinning period owing to deposition of nanoparticles into the triple contact line wedge. Wu et al established a multiphase thermal lattice Boltzmann (LB) model based on multiple distribution functions to study the evaporation process of micron-sized droplets in pits. Especially, the liquid film fracture behavior of evaporating droplets in the pit was captured in 2-TCL and 3-TCL modes.…”
Section: Introductionmentioning
confidence: 99%
“…Sefiane and Bennacer concluded that nanofluid droplets reduced the overall evaporation time compared to base fluid droplets but prolonged the pinning period owing to deposition of nanoparticles into the triple contact line wedge. Wu et al established a multiphase thermal lattice Boltzmann (LB) model based on multiple distribution functions to study the evaporation process of micron-sized droplets in pits. Especially, the liquid film fracture behavior of evaporating droplets in the pit was captured in 2-TCL and 3-TCL modes.…”
Section: Introductionmentioning
confidence: 99%
“…As a mesoscopic approach, the pseudopotential multiphase lattice Boltzmann method (LBM) tackles the statistical behavior of molecular ensembles and deals with the mean-field approximation of the molecular interaction, thus having much lower computational costs. Pseudopotential LBM has been widely used to simulate microscopic phenomena such as slippage, , liquid–vapor phase change heat transfer, and curvature dependency of the surface tension for nanobubbles and nanodrops. , Recently, Fei et al , demonstrated that a two-range pseudopotential LBM is able to achieve a positive disjoining pressure in the thin film separating bulk fluid of the other component, and proposed a mesoscopic model of binary fluid mixtures for the simulation of soft flowing systems. However, quantitative and systematic investigations on the disjoining pressure effect of nanoscale thin liquid films in contact with the solid surface are rare.…”
Section: Introductionmentioning
confidence: 99%